Non-invasive imaging of liquid/gas flow using ultrasonic transmission-mode tomography - Fazalul Rahiman, Mohd. Hafiz (2005)
Real-time process monitoring plays a dominant role in many areas of industry and scientific research concerning liquid/gas two-phase flow. It is proved that the operation efficiency of a process is closely related to accurate measurement and control of hydrodynamic parameters such as flow regime and flow rate. The ultrasonic tomography which has been developed recently for the liquid/gas visualization mostly implements the invasive systems. The invasive systems however could not withstand high pressure from the industrial pipeline besides it has a few disadvantages and limitations. Due to the disadvantages and the limitations of an invasive system therefore this thesis presents a non-invasive of ultrasonic tomography system to overcome the problems. By using 16-pairs of ultrasonic transducers, the electronic measurement circuits, the data acquisition system and suitable image reconstruction algorithms, the online measurement of a liquid/gas flow was realized. The system was capable of visualizing the internal characteristics of liquid and gas flow and provides the concentration profile for the corresponding liquid and gas flow. The results obtained are useful for the online monitoring of liquid/gas flow in flow regime, chemical mixture transportation or fluid transportation at sub-sea oil fields.